Gifts and Calling: Coming to Terms with Jews as Covenantal Partners - Cunningham, Philip A. (Studies in Christian-Jewish relations, 2017)
This article examines the theological terminology used in the 2015 Vatican statement, "The Gifts and the Calling of God Are Irrevocable." It particularly analyzes the words "salvation," "Christ," "promise and fulfillment," and the cluster of terms "evangelization, mission, witness, and dialogue." After noting that "Gifts and Calling" does not always carefully define its use of such expressions, and that Christians and Jews often understand even common terms in different ways, the essay also recommends terminological refinements as the Christian-Jewish dialogue further matures in the future.